2017
DOI: 10.3390/md15100304
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing and Characterization of Novel PII Signaling Protein Gene in Microalga Haematococcus pluvialis

Abstract: The PII signaling protein is a key protein for controlling nitrogen assimilatory reactions in most organisms, but little information is reported on PII proteins of green microalga Haematococcus pluvialis. Since H. pluvialis cells can produce a large amount of astaxanthin upon nitrogen starvation, its PII protein may represent an important factor on elevated production of Haematococcus astaxanthin. This study identified and isolated the coding gene (HpGLB1) from this microalga. The full-length of HpGLB1 was 122… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…5). This result suggested that PII may play a role in regulating astaxanthin biosynthesis (Ma et al, 2017). Nonetheless, PII targets in H. pluvialis must first be elucidated before any conclusion about PII function can be made.…”
Section: Functions Of Pii Derived From Gene Expression and Mutant Anamentioning
confidence: 99%
See 1 more Smart Citation
“…5). This result suggested that PII may play a role in regulating astaxanthin biosynthesis (Ma et al, 2017). Nonetheless, PII targets in H. pluvialis must first be elucidated before any conclusion about PII function can be made.…”
Section: Functions Of Pii Derived From Gene Expression and Mutant Anamentioning
confidence: 99%
“…In addition to N starvation and the effects of inorganic N (Ermilova et al, 2013;Ma et al, 2017;Zalutskaya et al, 2018), PII may be regulated by organic N. For instance, in P. parva, Arg supports the growth of this nonphotosynthetic alga and influences PII abundance, with high internal Arg concentrations corresponding to high PII levels (Lapina et al, 2019). However, the exact mechanism by which external Arg regulates PII levels awaits further studies.…”
Section: Functions Of Pii Derived From Gene Expression and Mutant Anamentioning
confidence: 99%
“…Furthermore, phosphorous is crucial in the transfer of energy within cells, membrane development and biosynthesis of nucleic acids and phospholipids [ 45 ]. Thus, limited availability of phosphorous in the growth media would adversely affect cell growth, and energy otherwise used in cell division would be transferred to carotenogenesis [ 24 , [46] , [47] , [48] ]. Nonetheless, numerous studies have reported that high phosphate concentrations could also inhibit the growth of microalgae due to the phenomenon identified as phosphorus toxicity, as further evinced by results of the present study [ 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, no homologues of PipX and NtcA are conserved in plants [ 12 ]. In representative plants, PII proteins are regulated at the transcriptional level [ 20 22 ]. In this study, we demonstrate that expression of Chlamydomonas PII is under the complex control of positive signals (i.e., nitrate and nitrite) and negative signals (NO), and GLB1 gene expression pattern is very similar to that observed for nitrate assimilation genes.…”
Section: Discussionmentioning
confidence: 99%
“…In Chloroplastida (green algae and land plants) PII-encoding GLB1 genes are nuclear-encoded and, in Rhodophyta they are coded by the plastid genome [ 6 ]. It is believed that regulation of PII in plants may be transcriptional [ 20 22 ]. However, unlike bacteria, the transcriptional control of plant PII expression remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%